2005
DOI: 10.1080/01926230590959866
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Potential of the Pig as a Model for the Vaginal Irritancy of Benzalkonium Chloride in Comparison to the Nonirritant Microbicide PHI-443 and the Spermicide Vanadocene Dithiocarbamate

Abstract: A porcine model was established to test the mucosal toxicity potential of a thiophene thiourea (PHI-443)-based anti-HIV microbicide and a vanadocene-based spermicide, vanadocene dithiocarbamate (VDDTC) in comparison to benzalkonium chloride (BZK). Nine domestic pigs (Duroc) in nonestrus stage received a single intravaginal application of 2% BZK, 2% PHI-443, or 0.1% VDDTC-containing gel. At various times after gel application, cell differentials and levels of inflammatory cytokines (IL-1β, IL-4, IL-6, IL-8, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Porcine vaginal mucosa was used for simulation of vaginal mucoadhesion due to similarity of porcine and human vaginas in terms of anatomical structure, pH, vaginal secretion and cervical mucus production. 32) Comparative studies of human and porcine vaginal mucosa revealed similarities in the morphology-both possess a nonkeratinized, stratified and squamous surface epithelium differentiated only in thickness (human: about 150-200 µm, porcine: 116 µm) and demonstrated the striking similarities in barrier composition and permeability. 19) Moreover, experiments with porcine mucosa application allow to replace highly expensive and requiring Bioethics Committee approval in vivo studies.…”
Section: Resultsmentioning
confidence: 99%
“…Porcine vaginal mucosa was used for simulation of vaginal mucoadhesion due to similarity of porcine and human vaginas in terms of anatomical structure, pH, vaginal secretion and cervical mucus production. 32) Comparative studies of human and porcine vaginal mucosa revealed similarities in the morphology-both possess a nonkeratinized, stratified and squamous surface epithelium differentiated only in thickness (human: about 150-200 µm, porcine: 116 µm) and demonstrated the striking similarities in barrier composition and permeability. 19) Moreover, experiments with porcine mucosa application allow to replace highly expensive and requiring Bioethics Committee approval in vivo studies.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of mucoadhesion involves a contact stage between the mucoadhesive and mucosal layer and a subsequently consolidation stage, that comprises several physicochemical interactions (including van der Waals and hydrogen bonds or electrostatic interactions) which strengthen the material-mucin connection, providing intimate and prolonged adhesion [49]. Porcine vaginal mucosa was used for the imitation of vaginal mucoadhesion due to the similarity of porcine and human vaginas in terms of anatomical structure, pH, and vaginal secretion [50]. The effect of CS concentration and β-GP crosslinking on the force of detachment (F max ) and work required to overcome the hydrogel-porcine vaginal mucosa interaction (W ad ) is presented in Figure 5A,B.…”
Section: Swelling Index and Mucoadhesion Studiesmentioning
confidence: 99%
“…Rabbits have a simple cuboidal or columnar epithelium that is highly sensitive to mucosal irritants when compared to the stratified squamous epithelium of the human vagina and remains the FDA-approved animal model for testing the acceptability of vaginal microbicides (36). In the rabbit model, repeated intravaginal administration of PHI-443 plus stampidine by a gel formulation at concentrations nearly 2,000 and 10,000 times higher than their respective in vitro anti-HIV IC 50 values did not result in vaginal irritation.…”
Section: Discussionmentioning
confidence: 99%